2018
DOI: 10.1007/s00420-018-1324-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual and psychological stress during computer work in healthy, young females—physiological responses

Abstract: PurposeAmong computer workers, visual complaints, and neck pain are highly prevalent. This study explores how occupational simulated stressors during computer work, like glare and psychosocial stress, affect physiological responses in young females with normal vision.MethodsThe study was a within-subject laboratory experiment with a counterbalanced, repeated design. Forty-three females performed four 10-min computer-work sessions with different stress exposures: (1) minimal stress; (2) visual stress (direct gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 97 publications
0
35
0
3
Order By: Relevance
“…When the eyes must adjust for a clear retinal image, the intensity of muscle activity in trapezius increases [3][4][5]. In a recent experimental study, an induced transient increase was found in trapezius muscle blood flow when the study participants' were exposed to moderate glare [6]. Even lower degrees of blur may cause impaired performance and visual discomfort, and people working in poor visual conditions are more likely to suffer from musculoskeletal disorders [7].…”
Section: Introductionmentioning
confidence: 97%
“…When the eyes must adjust for a clear retinal image, the intensity of muscle activity in trapezius increases [3][4][5]. In a recent experimental study, an induced transient increase was found in trapezius muscle blood flow when the study participants' were exposed to moderate glare [6]. Even lower degrees of blur may cause impaired performance and visual discomfort, and people working in poor visual conditions are more likely to suffer from musculoskeletal disorders [7].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, due to the high accuracy requirements for tasks such as inspection or manual assembly, workers tend to bend their necks forward to give optimal visual conditions and could cause shoulder symptoms [32]. Aghilinejad et al found that the use of magni cation loupes may improve the visibility of electronic parts as well as improving the postures of assembly workers and may reduce musculoskeletal discomfort [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, glare exposure has been reported to result in increased orbicularis oculi muscle activity and decreased aperture size (eyelid squinting), decreased pupil size, increased trapezius blood flow, altered eye movements, decreased reading performance, and reduced productivity (Berman et al 1994;Glimne et al 2015;Glimne et al 2013;Gowrisankaran et al 2007;Hemphälä and Eklund 2012;Lin et al 2015;Mork et al 2016;Mork et al 2018).…”
Section: Introductionmentioning
confidence: 99%